The relationship between emotional exhaustion and possible psychiatric disorders: Anxiety, depression and burnout in Medical students (Research, Society and Development, 2024)
Upon entering Medical school, there is a significant decline in mental health, which worsens as graduation progresses. Several factors are described as stressful environments in Medical students, such as the highly stressful academic environment, competitiveness, sleep deprivation, excessive workload, peer pressure, curricular, affective and institutional factors. The present study aims to analyze the spectrum of psychiatric manifestations in Medical students and the relationship with the mental exhaustion of these individuals. Burnout does not obviously depend on individual predisposing factors, such as emotional expression or means of coping with stress, but is also linked to external factors, such as the mold of the educational system, and can generate negative impacts on students' academic and personal lives. Among students in the clinical cycle, represented as being in the 3rd, 4th and 5th years, the prevalence of burnout was higher among students in the third and fourth years, and this higher prevalence may be due to the transition from basic sciences to clinical sciences. Institutional intervention, from faculty and educational support programs, is necessary for early recognition, a practical and targeted approach as mechanisms to contain clinical repercussions and personal losses to Medical students.